2022
DOI: 10.3390/cancers14246239
|View full text |Cite
|
Sign up to set email alerts
|

Different Oncologic Outcomes in Early-Onset and Late-Onset Sporadic Colorectal Cancer: A Regression Analysis on 2073 Patients

Abstract: The incidence of colorectal cancer (CRC) is increasing in the population aged ≤ 49 (early-onset CRC-EOCRC). Recent studies highlighted the biological and clinical differences between EOCRC and late-onset CRC (LOCRC-age ≥ 50), while comparative results about long-term survival are still debated. This study aimed to investigate whether age of onset may impact on oncologic outcomes in a surgical population of sporadic CRC patients. Patients operated on for sporadic CRC from January 2010 to January 2022 were alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
9
2
Order By: Relevance
“…Previous studies hypothesized that aggressive pathological features and advanced stage at diagnosis in EORC patients may be the cause for a worse response to neoadjuvant therapies [21,22,[25][26][27][28][29]. However, in the present study, and in previous studies by our group [9,10,15], we did not report any difference in pathological features between EOand LORC patients. Although it is well known that young patients are diagnosed at a more advanced stage [9,10,15], the present study-focused on preoperatively treated locally advanced RC patients-presented a very homogeneous population in terms of pretreatment MRI stage.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Previous studies hypothesized that aggressive pathological features and advanced stage at diagnosis in EORC patients may be the cause for a worse response to neoadjuvant therapies [21,22,[25][26][27][28][29]. However, in the present study, and in previous studies by our group [9,10,15], we did not report any difference in pathological features between EOand LORC patients. Although it is well known that young patients are diagnosed at a more advanced stage [9,10,15], the present study-focused on preoperatively treated locally advanced RC patients-presented a very homogeneous population in terms of pretreatment MRI stage.…”
Section: Discussioncontrasting
confidence: 94%
“…However, in the present study, and in previous studies by our group [9,10,15], we did not report any difference in pathological features between EOand LORC patients. Although it is well known that young patients are diagnosed at a more advanced stage [9,10,15], the present study-focused on preoperatively treated locally advanced RC patients-presented a very homogeneous population in terms of pretreatment MRI stage. Hence, neither pathological features nor stage disease at diagnosis resulted in the peculiar characteristic of EORC patients and could not be hypothesized as causes for a worse response.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…A multicenter study reported a better prognosis for EOCRC compared to LOCRC [ 117 ]. Conversely, a single-center retrospective study showed worse recurrence, PFS and cancer-specific survival for EOCRC compared to LOCRC [ 118 ]. A multicenter randomized trial [ 119 ] and a retrospective study from the Memorial Sloan Kettering Cancer Center [ 94 ] showed no significant difference in survival between patients with metastatic EOCRC and those with metastatic LOCRC.…”
Section: Treatmentmentioning
confidence: 99%
“…EOCRC patients have a low prevalence of family history (25%) and pathogenic cancer susceptibility genes (16%) [12]. The causes of EOCRC are unclear, and the cancer-related mortality of EOCRC patients may increase in the next decade [13,14]. Liu et al found that early-onset patients may have higher overall survival (OS) [15,16], but Gao et al found no difference in prognosis between EOCRC and LOCRC patients [17].…”
Section: Introductionmentioning
confidence: 99%